POLYPHASIC CHARACTERIZATION OF THREE STRAINS OF ANABAENA RENIFORMIS AND APHANIZOMENON APHANIZOMENOIDES (CYANOBACTERIA) AND THEIR RECLASSIFICATION TO SPHAEROSPERMUM GEN. NOV. (INCL. ANABAENA KISSELEVIANA)(1) - Zapomělová, Eliška; Jezberová, Jitka; Hrouzek, Pavel; Hisem, Daniel; Řeháková, Klára; Komárková, Jaroslava (Journal of phycology, 2009)
Occurrences of rare cyanobacteria Anabaena reniformis Lemmerm. and Aphanizomenon aphanizomenoides (Forti) Horecká et Komárek were recently detected at several localities in the Czech Republic. Two monoclonal strains of An. reniformis and one strain of Aph. aphanizomenoides were isolated from distant localities and different sampling years. They were characterized by a combination of morphological, genetic, and biochemical approaches. For the first time, partial 16S rRNA gene sequences were obtained for these morphospecies. Based on this gene, all of these strains clustered separately from other planktonic Anabaena and Aphanizomenon strains. They appeared in a cluster with Cylindrospermopsis Seenaya et Subba Raju and Raphidiopsis F. E. Fritsch et M. F. Rich, clustered closely together with two An. kisseleviana Elenkin strains available from GenBank. A new generic entity was defined (Sphaerospermum gen. nov., with the type species S. reniforme, based on the traditional species An. reniformis). These results contribute significantly to the knowledge base about genetic heterogeneity among planktonic Anabaena-like and Aphanizomenon-like morphospecies. Accordingly, the subgenus Dolichospermum, previously proposed for the group of planktonic Anabaena, should be revaluated. Secondary metabolite profiles of the An. reniformis and Aph. aphanizomenoides strains differed considerably from 17 other planktonic Anabaena strains of eight morphospecies isolated from Czech water bodies. Production of puwainaphycin A was found in both of the An. reniformis strains. Despite the relatively short phylogenetic distance from Cylidrospermopsis, the production of cylindrospermopsin was not detected in any of our strains.
Keywords: phytoplankton; secondary metabolites; Anabaena; 16S rRNA gene; morphology; taxonomy; cyanobacteria; new genus